Gross N2O Production Process, Not Consumption, Determines the Temperature Sensitivity of Net N2O Emission in Arable Soil Subject to Different Long-Term Fertilization Practices - Yin, Chang; Fan, Xiaoping; Yan, Guochao; Chen, Hao; Ye, Mujun; Ni, Liang; Peng, Hongyun; Ran, Wei; Zhao, Yuhua; Li, Tingqiang; Wakelin, Steven A.; Liang, Yongchao (Frontiers in Microbiology, 2020)
Chronic amendment of agricultural soil with synthetic nitrogen fertilization and/or livestock manure has been demonstrated to enhance the feedback intensity of net N2O emission to temperature variation (i.e. temperature sensitivity, TS). Yet few studies have explored the relevance of changes in underlying gross N2O production and consumption processes towards explaining this phenomenon, in particular for the latter. Furthermore, the microbe-based mechanisms associated with the variation of N2O consumption process remain largely unexplored. To address this knowledge gap, a temperature- (15, 25 and 35 o C) and moisture-controlled (50% water holding capacity) microcosm incubation experiment was established using an arable soil subject to longterm addition of synthetic fertilizer (NPK), a mixture of synthetic fertilizer with livestock manure (MNPK), or with no fertilizer treatment (CK). Over the incubation time period, the C2H2 inhibition method was adopted to monitor reaction rates of gross N2O production and consumption; the population sizes and community structures of nosZI-and nosZII-N2O reducers were analyzed using quantitative PCR (Q-PCR) and terminal restriction fragment length polymorphism (T-RFLP). The results indicated that only NPK significantly increased the TS of net N2O emission, and gross N2O consumption process consistently occurred under all treatment combinations (temperature and fertilization) at each sampling time point. The responses of gross N2O production and consumption processes to temperature elevation exhibited fertilization-and sampling time-dependent pattern, and the higher net N2O production TS in the NPK treatment was underlain by its higher TS of gross production process and insensitivity of gross consumption process to temperature. The size and structure of nosZII-N2O reducers, as well as the community structure of nosZI-N2O reducers, were positively correlated with variation of gross N2O production and consumption rates across all fertilization regimes. NosZII-N2O reducer abundance was less responsive to temperature change, and its community structure less susceptible to fertilization, as compared with nosZI-N2O reducers.Overall, our results demonstrate that the TS of the gross N2O production process, not gross consumption, is the key step regulating the TS of net N2O production, and both nosZI-and nosZII-N2O clades are likely active N2O reducers in the tested soil.